Cd2+-induced Fluorescent Metallogel: A Case of CHEF and ACQ Phenomena - Dixit M.K.; Mahendar C.; Dubey M. (My University, 2025)
A fluorescent metallogel (1 %w/v) has been synthesized from deprotonation of a non-fluorescent adipic acid-derived ligand H2AL with LiOH followed by coordination with Cd2+ in DMF. Cd2+ not only induces the coordination complex formation but also leads to aggregation, formation of nanofibers of about ≈12 nm average diameter and gelation. The metallogel was also found to be reversibly stimuli-responsive towards heating and mechanical shaking whereas it was resistant to ultrasound. The involvement of chelation-enhanced fluorescence (CHEF), aggregation-induced emission (AIE) and aggregation-caused quenching (ACQ) during the course of gelation has been well established by fluorescence experiments. Further, the coordination complex involved in metallogel formation has been well characterized by ESI-MS and Job's plot. The synthesized metallogel has a true gel phase as shown by detailed rheological studies. The mechanism of gelation is well established by using FTIR, UV-vis, fluorescence, lifetime measurement, Job's plot, ESI-MS, PXRD and TEM techniques. © 2019 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.